(untitled) (Applied Biological Research, 2017)
Renal secondary hyperparathyroidism is a complication of chronic renal failure. It is clinically characterized by hyperostotic bone lesions such as facial swelling due to the deposition of unmineralized osteoid by hyperplastic osteoblasts and production of fibrous connective tissue exceed the rate of bone resorption and increased endogenous levels of parathyroid hormone (PTH) (Aiello et al., 2015). Although secondary renal hyperparathyroidism and renal osteodystrophy are well known sequel of chronic renal failure (CRF) but clinically important renal osteodystrophy is rarely seen in dogs (Nagode et al., 1996, Rusenov et al., 2009; Chand et al., 2012). This paper presents two cases of fibrous osteodystrophy with facial hyperostosis associated with renal secondary hyperparathyroidism in dogs.